Organisational Learning and Adaptation in Non-formal ‎Vocational Education: A Phenomenological Inquiry into ‎Institutional Resilience Under VUCA Conditions - Alim Harun Pamungkas; Rizki Putri Ramadhani; Sherlyane Hendri; Anggi Firmanjaya Saputra; Putra Ramadani; Handriva Fauzi (Yayasan Darussalam Bengkulu, 2026)
Nonformal vocational education and training providers frequently operate under unstable funding, fragmented regulation, market uncertainty, and limited policy protection, yet little is known about how organisational learning enables their long-term adaptation. This study examined how LKP Oase Academy, a spa-therapy training institution established in Malang, Indonesia, learned and adapted across more than two decades of environmental adversity. A qualitative phenomenological design was employed to analyse the lived organisational experiences of six informants representing managerial, instructional, administrative, partnership, and alumni perspectives. Data were generated over fourteen months through in-depth semi-structured interviews, observation, and documentary analysis, and were analysed through data condensation, phenomenological meaning clustering, and iterative coding. The analysis reconstructed twenty organisational phases between 2002 and 2025 and identified three interconnected adaptive mechanisms: curriculum and pedagogical repositioning, strategic market and partnership reconfiguration, and financial and operational restructuring. These mechanisms emerged in response to market formation difficulties, occupational stigma, reputational contestation, regulatory fragmentation, curriculum displacement by formal vocational schools, the COVID-19 pandemic, and the founder's serious illness. The findings show that organisational adaptation was enabled by the cumulative conversion of adversity into regulatory knowledge, documentary safeguards, partnership routines, revised curricula, and operational procedures. The study introduces ketahanmalangan, or adversity-driven institutional resilience, to explain a historically accumulated form of resilience that is biographically mediated, organisationally institutionalised, and critically shaped by structural precarity. The findings imply that VET policy should strengthen inter-ministerial coordination and complementarity between formal and nonformal providers, while institutional leaders should distribute tacit knowledge, formalise learning, and strengthen succession and partnership governance.